Community-Based Circular Economy Practices and Social Innovation: A Case Study from Bone Regency, Indonesia - Ismail, Ismail; Syam, Anita; H, Firman; Marhati, Marhati; MR, Syarifa Aeni (Universitas Medan Area, 2025)
This study examines the implementation of circular economy practices and their contribution to social innovation and strengthening the local economy in Bone Regency, South Sulawesi. The research was motivated by the high volume of agricultural and fishery waste that has not been optimally managed, as well as the potential of inorganic materials that can be reused as products with commercial value. This study employs a qualitative approach with a case study design, involving 15 informants comprising micro-entrepreneurs, village officials, community leaders, youth groups, and community facilitators. Data were collected through in-depth interviews, observations, and document reviews, and analyzed using the interactive model of Miles and Huberman. The research findings revealed six main themes: utilization of agricultural and fishery waste, reuse of inorganic materials, community collaboration, environmental education, regulatory support, and institutional challenges. The results show that circular economy practices in Bone evolve through, supported by local institutions and cultural values of cooperation. These practices diversify income, raise environmental awareness, and create a more inclusive social ecosystem, though challenges remain in digital marketing and institutional capacity. The study highlights the importance of multi-stakeholder collaboration and adaptive policy support to sustain the circular economy at the local level and demonstrates its potential as a replicable model for other rural areas in Indonesia.